Wiley CPA exam review, 2012-2013 - Whittington, O.Ray , 1948-; Delaney, Patrick R. (Wiley, 2012)
The #1 CPA exam review self-study leader The CPA exam review self-study program more CPA candidates turn to take the test and pass it, Wiley CPA Exam Review 39th Edition contains more than 4,200 multiple-choice questions and includes complete information on the Task Based Simulations